Allergenicity of Additives for Ointment Base - TODA, Kiyoshi; OTA, Midori (Skin research, 1985)
Three patients with contact dermatitis caused by Amerchol CAB, an ointment base additive used in Fluocinonide ointment were examined for allergenicity. Eight patients with other forms of contact dermatitis and a control group of 5 volunteers were patch tested for lanolin, lanohydro, lanolin alcohol, and Amerchol CAB using the Finn Chamber. The reactions were graded according to the ICDRG after 48, 72, and 96 hours. Three out of the 11 cases showed a positive reaction to all the parameters. These reactions were thought to be elicited by some impurities in Amerchol CAB and lanolin derivatives.